Analysis of the Analytical Junior High School Deaf Students’ Thinking Ability in SMPLBN Ungaran (Journal of Innovative Science Education, 2019)
This study aims to determine the ability of analytic thinking students especially deaf students. Analytic is included in thinking skills that lead students to become independent thinkers and able to demonstrate the quality of students' abilities. There are 3 stages in analytic thinking, namely differentiating, attributing and connecting. The method used in the study is mixed methods with concurent strategies. The subject of this research is State Public High School for Deaf students. The improvement of students' analytical thinking ability is 0.22 and included in the low category. The results of the percentage value of deaf students for differentiating indicators was 56.94%, attributed to 43.05%, and linking by 71.11%.